Testing the Stability of Systematic Risk Coefficient of the Stocks Listed in Damascus Securities Exchange - Mourhij, Mounzer (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إنّ الهدف من هذا البحث هو اختبار مدى استقرار قيم معاملات المخاطرة المنتظمة للأسهم المسجلة في سوق دمشق للأوراق المالية، وتقرير إمكانية الاعتماد على قيمها المقدّرة في حساب معدّلات العوائد المطلوبة على الاستثمارات الفردية في تلك الأسهم أو على محافظ الاستثمار المشكّلة منها. وقد قام الباحث بجمع البيانات المطلوبة (أسعار إقفال المؤشر العام لسوق دمشق للأوراق المالية والأسهم المسجلة فيه) خلال الفترة الممتدة من 4/1/2010 ولغاية 28/10/2013 من خلال الموقع الالكتروني للسوق. تمّ استخدام البيانات لتقدير قيم معاملات المخاطرة المنتظمة (بيتا) للأسهم المدروسة، ومن ثمّ اختبار مدى استقرار القيم المقدّرة لمعاملات بيتا للأسهم اعتماداً على أسلوب استخدام الزمن كمتغير في دالة الانحدار المستخدمة لتقدير قيم معاملات بيتا وذلك خلال كامل فترة الدراسة وخلال ثلاث فترات جزئية جرى تقسيمها بحيث تشمل كل منها خمس فترات ربع سنوية، وقد تمّ بعد ذلك الحكم على مدى استقرار قيم المعاملات المختبرة اعتماداً على نتائج اختبار معنوية معاملات متغير الزمن المستخدم. وقد توصل الباحث إلى نتائج تفيد بميل غالبية معاملات المخاطرة المنتظمة للأسهم المدروسة إلى الاستقرار عبر الزمن وبنسبة تفوق الـ 80% منها، مما يعني إمكانية الاعتماد على قيم بيتا المقدّرة لحساب معدّل العائد المطلوب على أيّ سهم فردي أو محفظة استثمارات مشكّلة من تلك الأسهم المسجلة في سوق دمشق للأوراق المالية، وبالتالي اتخاذ القرار الاستثماري المناسب بناءً على ذلك. The objective of this research is to test the stability of systematic risk coefficients of stocks listed on the Damascus Securities Exchange through the period (4/1/2010 – 28/10/2013), and therefore the ability to use the values of these coefficients to calculate the required rate of return on investment in the individual stocks and portfolios. The data related to the closed prices of stocks and market index were collected from the website of DSE, which is used to estimate the values of systematic risk (Beta). Then the researcher has tested the stability of the coefficients throughout the entire period and the three sub-periods each one consists of five yearly quarters by using the time as a variable in the regression model, and by testing the significance of the coefficient of time variable. The results of the research show that greater than 80% of these coefficients were insignificant, that is, the higher percentage of stocks have a stable Beta, and can be used to calculate the required rate of return on investment, therefore suitable investment decisions may be made upon these results.